Non-cystic fibrosis bronchiectasis: Etiologic approach and effects of long-term azithromycin in children (Annals of Medical Research, 2021)
Aim: Non-cystic fibrosis bronchiectasis (NCFB) is a chronic pulmonary problem that includes a group of heterogeneous diseases. Macrolide antibiotics are increasingly prescribed for patients with NCFB, but there are very few studies on their use in children. This study aimed to search the clinical features of children with NCFB and the effect of long-term use of azithromycin on the frequency of aggravation, microbiological reproduction, and pulmonary function tests.Materials and Methods: A total of 79 cases diagnosed with NCFB were recorded. Clinical, laboratory, and radiological evaluations were also recorded. Exacerbation frequency, sputum cultures, and pulmonary function tests of 27 children who received azithromycin before and during prophylaxis were also analyzed.Results: The median age of children was 7.6 years old (1 to 16 years), when the children were diagnosed with NCFB. Bronchiectasis etiology was detected in 62 patients. Primary ciliary dyskinesia (PCD) was the most common cause of bronchiectasis, which 24 (30%) children were diagnosed with PCD. Azithromycin treatment was given to 27 bronchiectasis patients for six months. A statistically significant decrease was detected in pulmonary aggravation frequency and sputum microbiology during azithromycin treatment (p 0.05)Conclusion: The use of azithromycin in children with NCFB improves aggravation frequency but has no significant effect on the pulmonary function test.
Keywords: Azithromycin; non-cystic fibrosis bronchiectasis; primary ciliary dyskinesia; pulmonary exacerbation